2022
DOI: 10.1177/17534259221097835
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 is produced by monocyte-derived and alveolar macrophages, and is not associated with the severity of idiopathic pulmonary fibrosis

Abstract: The soluble form of the membrane hemoglobin scavenger receptor CD163 (sCD163), released by shedding, is a strong marker for macrophage activation. Serum sCD163 levels rise in several acute inflammatory states and some fibrosing diseases. Monocyte-derived macrophages (MoDM) differentiated by macrophage colony-stimulating factor (M-MoDM) contribute to the pathophysiology of idiopathic pulmonary fibrosis (IPF), an irreversible and rapidly fatal interstitial lung disease. Since M-MoDM express high membrane CD163 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…CHIT1 [73], EGR1 [74], S100A12 [75], CD163 [76] and S100A8 [77] have a critical role in initiating COPD. CHIT1 [78], EGR1 [79], ATF3 [80], S100A12 [81], CD163 [82] and S100A8 [81] were significantly associated with idiopathic pulmonary fibrosis. CHIT1 [83], EGR1 [84], ATF3 [85], XIST (X inactive specific transcript) [86], CD163 [66] and S100A8 [87] level were significantly altered in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…CHIT1 [73], EGR1 [74], S100A12 [75], CD163 [76] and S100A8 [77] have a critical role in initiating COPD. CHIT1 [78], EGR1 [79], ATF3 [80], S100A12 [81], CD163 [82] and S100A8 [81] were significantly associated with idiopathic pulmonary fibrosis. CHIT1 [83], EGR1 [84], ATF3 [85], XIST (X inactive specific transcript) [86], CD163 [66] and S100A8 [87] level were significantly altered in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while data presented here show that the levels of sCD163 were reduced in severely ill patients, other studies have shown that sCD163 levels increase with disease severity [ 27 ]. This discrepancy could be a reflection of variations in methodology, sample collection timing, and/or differences in macrophage activity [ 28 ]. Irrespective of these discrepancies, variations in sCD163 concentration seem to have little, if any, impact on COVID-19 disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanisms behind this regulation remain unknown [52]. In addition to the cell membrane form, CD163 and CD206 be shed upon bacterial stimulation, generating soluble forms [53][54][55], which can be used as biomarkers for different diseases [56][57][58]. In this study, AMM and MDM responses were determined for a short interval in vitro, and the soluble forms of these proteins were not measured [11].…”
Section: Plos Onementioning
confidence: 99%